2014
DOI: 10.1073/pnas.1422649112
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic photonic crystals realized through DNA-programmable assembly

Abstract: Three-dimensional dielectric photonic crystals have well-established enhanced light-matter interactions via high Q factors. Their plasmonic counterparts based on arrays of nanoparticles, however, have not been experimentally well explored owing to a lack of available synthetic routes for preparing them. However, such structures should facilitate these interactions based on the small mode volumes associated with plasmonic polarization. Herein we report strong lightplasmon interactions within 3D plasmonic photon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
148
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 110 publications
(155 citation statements)
references
References 32 publications
6
148
0
Order By: Relevance
“…This suggests that the interparticle plasmonic interactions here are primarily coherent and in-phase; small displacements (relative to their radii) in nanoparticle position do not meaningfully change the weak plasmonic coupling between particles. In turn, many of the emergent plasmonic and photonic effects that we have identified in similar systems (29,34,39) are likely robust to the presence of defects and forgiving to minor variations to the crystalline environment.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…This suggests that the interparticle plasmonic interactions here are primarily coherent and in-phase; small displacements (relative to their radii) in nanoparticle position do not meaningfully change the weak plasmonic coupling between particles. In turn, many of the emergent plasmonic and photonic effects that we have identified in similar systems (29,34,39) are likely robust to the presence of defects and forgiving to minor variations to the crystalline environment.…”
Section: Resultsmentioning
confidence: 79%
“…We have previously implemented volume-fraction-based methods with predictable and consistent agreement between experiment and simulation in the far field (28,29,32,34,39). Many of the unique and exciting plasmonic materials that we have explored using programmable DNA assembly depend solely on dipolar interparticle interactions (at low volume fraction) and are fairly insensitive and defect-tolerant.…”
Section: Discussionmentioning
confidence: 99%
“…Such superstructures behave as 3D plasmonic microcavities (passive cavities) that exhibit both guided modes and plasmonic near-field effects throughout the cavity medium. Therefore, upon incorporating excitonic materials into these superlattices, the nature of such 3D plasmonic microcavities (active cavities) can be explored systematically through an analysis of excitonic emission properties.In this work, we synthesize dye-functionalized plasmonic superlattices via DNA programmable assembly (10,14), and study their emission properties both experimentally and theoretically. …”
mentioning
confidence: 99%
“…Therefore, these methods provide exciting possibilities for controlling the interaction between photonic modes of microcavity structures and plasmonic modes of the highly polarizable nanoparticles for nano-/micrometer-scale optical applications. Indeed, it was recently demonstrated that one can control the strength of coupling between Fabry-Perot modes and localized surface plasmons in a body-centered cubic (bcc) crystal composed of gold nanoparticles with a rhombic dodecahedron (RD) crystal habit (14). Such superstructures behave as 3D plasmonic microcavities (passive cavities) that exhibit both guided modes and plasmonic near-field effects throughout the cavity medium.…”
mentioning
confidence: 99%
See 1 more Smart Citation